Cross-cultural differences in the Parent Rated Social Responsiveness Scale (SRS)? Evaluation of the Finnish version among high-functioning school aged males with and without autism spectrum disorder. (January 2015) - Jussila, Katja; Kuusikko-Gauffin, Sanna; Mattila, Marja-Leena; Loukusa, Soile; Pollock-Wurman, Rachel; Joskitt, Leena; Ebeling, Hanna; Moilanen, Irma; Pauls, David; Hurtig, Tuula
Highlights: The Finnish version of the Social Responsiveness Scale was evaluated in a clinical ASD sample. Reliability and validity of the instrument were found to be good. It is essential to determine the normative range for imported questionnaire in various cultures. Abstract: When importing screening questionnaires of ASD, it has been found that parental interpretation/reporting of autistic traits may be culturally influenced. In the current study, our aim was preliminary evaluation of the Finnish parent rated SRS in order to determine whether the measure would show promise as an aid in screening. The study sample consisted of high-functioning school aged male ASD outpatients of Oulu University Hospital ( n = 44, age 11.4 ± 2.3) and age-matched controls ( n = 44, age 11.8 ± 2.4 years). Internal consistency as well as convergent and discriminative validity was in line with previous research. However, the results indicated that the cut-off published in the SRS manual might be too high to be used in Finland. Our results emphasize the importance of determining the normative range and clinical cut-offs in various cultures when importing diagnostic screening questionnaires in order to avoid getting high percentages of false negatives in the screening phase, and thus risk leaving many children without adequate diagnostic evaluation and rehabilitation.